Uganda : Sixth Review Under the Policy Support Instrument and Request for an Extension of the Policy Support Instrument-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Sixth Review for Uganda Under the Policy Support Instrument. Structural rigidities continue to pose challenges to macroeconomic management in Uganda. Persistent weaknesses in project implementation coupled with rigidities in domestic financial markets limited the scope for fiscal and monetary stimulus in 2008/09. Progress with structural reforms has been uneven and may not have kept pace with the needs raised by the public investment drive. Macroeconomic policies will continue to aim at overcoming infrastructure bottlenecks while mitigating the impact of external shocks on domestic activity.